Retinal Map of Peripheral Retinal Degenerations and Tears. Part 3. Vitreoretinal Retinal Degeneration - V. A. Shaimova; N. A. Klyuchko; G. R. Islamova; T. B. Shaimov; S. Kh. Kuchkildina; R. B. Shaimov; A. A. Askaeva; M. S. Ivin; A. V. Fomin (Oftalʹmologiâ, 2025)
This work describes the results of a multimodal examination of patients with rhegmatogenous peripheral vitreoretinal degenerations. Objective: to conduct a multimodal study of rhegmatogenous peripheral vitreoretinal degenerations and present an informative retinal map of peripheral retinal degenerations and breaks. Methods. Multimodal diagnostics included traditional and additional methods: the ultra-widefield fundus imaging with the Clarus 500 or VISUCAM 500 (Carl Zeiss Meditech Inc., Dublin, USA) and wide-field OCT scanning of the retina periphery with SOLIX and RTVue XR Avanti (Optovue Inc. USA). Results. During the period of 2014–2024, 614 patients (959 eyes) were examined and 1304 peripheral degenerations and retinal breaks were identified with the multimodal examination. Regmatogenic (vitreoretinal) degenerations were found in 437 patients: lattice degeneration — 197 (15.1 %), “snail track” — 95 (7.29 %); vitreoretinal tufts — 145 (11.12 %). Based on the study results, an informative map of the main peripheral retinal degenerations has been developed. Conclusion. In this article (part 3) the multimodal study of peripheral dystrophies allowed us to present the retinal map of regmatogenic peripheral degenerations and retinal breaks for the purpose of timely detection and adequate treatment.